The Relationship Between Surgeon Gender and Stress During the Covid-19 Pandemic. Issue 4 (April 2021) - Mavroudis, Catherine L.; Landau, Sarah; Brooks, Ezra; Bergmark, Regan; Berlin, Nicholas L.; Blumenthal, Blanche; Cooper, Zara; Hwang, Eun Kyeong; Lancaster, Elizabeth; Waljee, Jennifer; Wick, Elizabeth; Yeo, Heather; et al.
Abstract : Objective: To investigate the relationship between surgeon gender and stress during the Covid-19 pandemic. Background: Although female surgeons face difficulties integrating work and home in the best of times, the Covid-19 pandemic has presented new challenges. The implications for the female surgical workforce are unknown. Methods: This cross-sectional, multi-center telephone survey study of surgeons was conducted across 5 academic institutions (May 15–June 5, 2020). The primary outcome was maximum stress level, measured using the validated Stress Numerical Rating Scale-11. Mixed-effects generalized linear models were used to estimate the relationship between surgeon stress level and gender. Results: Of 529 surgeons contacted, 337 surgeons responded and 335 surveys were complete (response rate 63.7%). The majority of female respondents were housestaff (58.1%), and the majority of male respondents were faculty (56.8%) ( P = 0.008). A greater proportion of male surgeons (50.3%) than female surgeons (36.8%) had children ⩽18 years ( P = 0.015). The mean maximum stress level for female surgeons was 7.51 (SD 1.49) and for male surgeons was 6.71 (SD 2.15) ( P < 0.001). After adjusting for the presence of children and training status, female gender was associated with a significantly higher maximum stress level ( P < 0.001). Conclusions: Our findings that women experienced more stress than men during the Covid-19 pandemic, regardless of parental status, suggest that there is more to the gendered differences in the stress experience of the pandemic than the added demands of childcare. Deliberate interventions are needed to promote and support the female surgical workforce during the pandemic. Abstract : Supplemental Digital Content is available in the text